From Kiruna to Giron - Briz Toriello, Mariana (2024)
This independent project addresses the decolonization of the Kiirunavaara Mine’s landscape post-closure, focusing on landscape remediation, reclamation, and rehabilitation guided by Sami perspectives to promote the return of the ecosystem services, focusing on reindeer herding. Indigenous communities have the right to self-determination and deserve the restoration of their lands. This project serves as an example of decolonization and sets a precedent for land rehabilitation as other mines across Sweden close. The project identifies a research gap due to limited literature on the decolonization of mines and the return of land to indigenous peoples. It specifically explores how the decolonization of the Laevas and Gabna Sami Villages' winter pastures, encroached by the Kiirunavaara mine, could be achieved. To address these objectives, the research includes a comprehensive literature review on the historical and physical context of the area, theories on decolonization and sense of place, and the Sami concept of meahcci to start understanding their perspective on the landscape. Site analysis through visits and mapping exercises, along with art analysis of Duodji, roughly translated to Sami art, further inform the project. The outcome is a conceptual proposal integrating remediation, reclamation, and rehabilitation practices, presented through three consecutive scenarios spaced 15 years apart, representing the transition from Kiruna to Giron. Key findings highlight the importance of participation and community involvement in the decolonization process, which spans decades. The project reflects an understanding of landscape decolonization through traditional Sami knowledge, learned from Sami sources, and Sami art analysis, extended to the landscape design. However, it acknowledges limitations, particularly the absence of direct Sami participation, which is a significant gap in the research and design process. In conclusion, this thesis proposes a design solution for the remediation of the Kiirunavaara mine and calls ...